Managing Refractory Myasthenia Gravis In-Depth Multidisciplinary Exploration: Case Report - Kentanto, Given; Sunaryo, Sunaryo (Jurnal Ners, 2024)
Our case of a 38-year-old female patient with refractory Myasthenia Gravis (MG) is presented, emphasizing the intricate and evolving nature of the disease. The patient exhibits predominant cranial and upper respiratory muscle involvement, characteristic of ocular MG, accompanied by diurnal symptom variation. The case underscores the imperative of individualized therapeutic strategies aimed at achieving disease stability and enhancing the patient's quality of life. Additionally, it highlights the pressing need for ongoing research and advancements in MG management, emphasizing tailored care and a multidisciplinary approach to address refractory cases effectively. This clinical journey exemplifies the complexities and opportunities inherent in the management of refractory MG within the context of contemporary medical practice.